Diversification benefits in the Finnish commercial property market - Falkenbach, Heidi (International Journal of Strategic Property Management, 2009)
The Finnish commercial property market internationalised rapidly in the beginning of the 21st century. According to the portfolio theory and previous research on international property investments, the main motivation factor driving international real estate investments is the possibility to reach diversification benefits. The paper discusses the diversification benefits offered by the Finnish property market in its early years of internationalisation. As international real estate investors in the Finnish property market include investors with both real estate only, as well as mixed‐asset portfolios, the diversification benefits are studied both in terms of a Finnish mixed‐asset portfolio, as well as international real estate portfolio. First Publish Online: 18 Oct 2010